THE STRUGGLE OF IDENTITY IN RELIGION PLURALITY IN VILLAGE OF EKASARI JEMBRANA, BALI - Widastra, Paskalis Nyoman; Anom Kumbara, A.A. Ngurah; Wirawan, A.A. Bagus; Mudana, I Gede (E-Journal of Cultural Studies; Volume 13, Number 2, May 2020, 2020)
The three religious communities in Ekasari Village come from a number of regencies in Bali. Only a small proportion of its members come from outside the island. They came in different time periods at the beginning of the 20th century (1930) and then formed their own communities based on religion in accordance with their respective histories. Even though they are separated in religion, administratively they are an area in the village office. The existence of these three communities is colored by identity struggles so it is interesting to be further investigated in cultural studies. The purpose of this study is (1) to understand the form of identity struggles that occur in Ekasari village, (2) understanding the ideology that works behind the identity struggle and (3) analyzing the implications of this identity struggle. This research approach uses qualitative analysis methods. Data collection techniques carried out by in-depth interviews, observation, and document analysis. Based on this research method it is found that there are certain ideologies that cause identity struggles found in the dynamics of religious, cultural, political and economic life of the people. The implication is that each religious community strives to fight for and maintain its identity while still trying to build communication through existing means. Keywords: community, identity struggle, ideology, communication